Geometric and Dosimetric Changes in Tumor and Lung Tissue During Radiotherapy for Lung Cancer With Atelectasis - Chen, Hua; Shao, Yan; Gu, Xiaohua; Zheng, Zhijie; Wang, Hao; Gu, Hengle; Duan, Yanhua; Feng, Aihui; Huang, Ying; Gan, Wutian; Chen, Chongyang; Xu, Zhiyong (Frontiers in Oncology, 2021)
Background and purpose: This article retrospectively characterized the geometric and dosimetric changes in target and normal tissue during radiotherapy for lung cancer patients with atelectasis. Materials and methods: A total of 270 cone beam computed tomography (CBCT) scans of 18 lung patients with atelectasis were collected. The degree and time of resolution or expansion of the atelectasis was recorded. The geometric, dosimetric and biological changes in the target and lung tissue were also quantified. Results: 2 patients with expansion, 4 patients with complete regression, 6 patients with partial regression and 6 patients with no change. The time of resolution or expansion varied. The tumor volume increased by 3.8% in the first 7 fractions, then decreased from the 9th fraction, and by 33.4% at the last CBCT. In the LR direction, the average COM, boundaries of the tumors gradually shifted mediastinally. In the AP direction, the COM of the tumors was shifted slightly in the posterior direction and then gradually shifted to the anterior direction, the boundaries of the tumors all moved mediastinally. In the SI direction, the COM of the tumors on the right side of the body was substantially shifted toward the head direction. the boundaries of the tumors varied greatly. D2, D98, Dmean, V95, V107 and TCP of the PTV were reduced during radiotherapy and were reduced to their lowest values during the last two fractions. The volume of the ipsilateral lung tended to increase gradually. The V5, V10, V20, V30, V40 and NTCP of the total lung gradually increased with the fraction. Conclusions: For most patients, regression of the atelectasis occurred and the volume of the ipsilateral lung tended to increase while the tumor volume decreased, and the COM and boundary of the tumors shifted toward mediastinum, which caused an insufficient dose to the target and an overdose to the lungs. Regression or expansion may occur for any fraction, and it is therefore recommended that CBCT be performed at least every other day.